2015
DOI: 10.1016/j.cell.2015.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Phase Separation by Low Complexity Domains Promotes Stress Granule Assembly and Drives Pathological Fibrillization

Abstract: SUMMARY Stress granules are membrane-less organelles composed of RNA-binding proteins (RBPs) and RNA. Functional impairment of stress granules has been implicated in amyotrophic lateral sclerosis, frontotemporal dementia and multisystem proteinopathy - diseases that are characterized by fibrillar inclusions of RBPs. Genetic evidence suggests a link between persistent stress granules and the accumulation of pathological inclusions. Here we demonstrate that the RBP hnRNPA1 undergoes liquid-liquid phase separatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

112
2,901
7
6

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 2,306 publications
(3,026 citation statements)
references
References 50 publications
(89 reference statements)
112
2,901
7
6
Order By: Relevance
“…The maturation of liquid droplets into aggregates has been reported for the ALS‐associated proteins FUS (Patel et al , 2015), TDP‐43 (Schmidt & Rohatgi, 2016), and hnRNPA1 (Molliex et al , 2015). After LLPS, these proteins transition from an initial liquid droplet state, through a gel‐like state of high viscosity, to a final stable aggregated form (Lin et al , 2015).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…The maturation of liquid droplets into aggregates has been reported for the ALS‐associated proteins FUS (Patel et al , 2015), TDP‐43 (Schmidt & Rohatgi, 2016), and hnRNPA1 (Molliex et al , 2015). After LLPS, these proteins transition from an initial liquid droplet state, through a gel‐like state of high viscosity, to a final stable aggregated form (Lin et al , 2015).…”
Section: Discussionmentioning
confidence: 87%
“…Recent studies revealed that the RNA binding and stress granule‐associated proteins FUS (Patel et al , 2015), hnRNPA1 (Molliex et al , 2015), and TDP43 (Conicella et al , 2016) have the ability to reversibly form intracellular membrane‐less organelles. These reversible droplets represent physiologically active protein or protein‐nucleic acid “bioreactors” (Hyman et al , 2014), which form through a process known as LLPS (Brangwynne et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These bodies, in contrast to classic organelles, locally enrich components within defined boundaries despite the lack of an outer membrane. Nucleoli (Brangwynne et al , 2011), P granules (Brangwynne et al , 2009), and stress granules (Molliex et al , 2015; Patel et al , 2015), three membrane‐less organelles, were recently reported to have liquid droplet properties (Brangwynne, 2013), supporting a role for liquid–liquid phase separation in their formation (Li et al , 2012b; Nott et al , 2015; Patel et al , 2015). The recruitment of additional components to these bodies is not well understood but must involve protein/protein interactions (Tourrière et al , 2003).…”
Section: Introductionmentioning
confidence: 99%